SISTEM PEMBELAJARAN FIQH TERINTEGRASI DI MADRASAH IBTIDAIYAH PESANTREN ANAK SHOLEH BAITUL QUR’AN GONTOR - Syarifah Syarifah; Akhmad Ikhwan Nur Aziz (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to describe and analyze the implementation of the learning system for fiqh material at the Madrasah Ibtidaiyah Pesantren Anak Sholeh Baitul Qur'an Gontor, particularly in terms of curriculum, methods, media, and learning evaluation, as well as to identify the supporting and inhibiting factors in its implementation. Method: This study uses a qualitative approach with descriptive analysis methods. Data were obtained through observation, indepth interviews, and documentation of the madrasah principal, fiqh teachers, and fiqh learning activities. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, with data validity reinforced through source and technique triangulation. Results: The results showed that the fiqh learning system in the madrasah had been implemented in an integrated and systematic manner. The fiqh curriculum was applied contextually through worship activities and religious habits. Varied learning methods and the use of relevant media were able to increase student engagement and understanding. Learning evaluation is conducted comprehensively by assessing the cognitive, affective, and psychomotor domains. The main supporting factors include teacher competence, a conducive madrasah environment, and student enthusiasm, while the inhibiting factors include time constraints and learning facilities.